Molecular Detection of Bacterial Pathogens in Flies as Potential Vectors from Surabaya Traditional Markets - Wahyuningtyas, Puput Ade; Kurniabudhi, Marek Yohana; Nugroho, Eko Prasetyo (Universitas Airlangga, 2025)
Flies are insects that act as mechanical vectors in the spread of disease, especially in environments with poor sanitation, such as traditional markets. Surabaya has several traditional markets with relatively poor hygiene, which poses a risk of becoming breeding grounds for flies carrying pathogens. This study aims to identify fly species and detect the presence of pathogenic bacteria, especially Escherichia coli and Salmonella spp., using the Polymerase Chain Reaction (PCR) method. This study employed purposive sampling and collected samples at five traditional market locations throughout the city of Surabaya. Morphological identification revealed that Musca domestica (89.78%) was the dominant species, followed by Chrysomya megacephala (9.43%), Chrysomya saffranea (0.3%), Lucilia sp. (0.41%), and Sarcophaga sp. (0.08%). The result of bacterial culture on selective media and PCR confirmation showed the presence of Escherichia coli (100%) in fly samples, while in SSA media, which was continued with biochemical tests, the results did not detect Salmonella (0%) bacteria. These findings confirm that market flies, particularly Musca domestica, can serve as vectors of pathogenic bacteria and have the potential to transmit diseases to humans. Therefore, monitoring and controlling fly populations in traditional markets is necessary as a preventive measure to maintain public health.